Pengembangan Sparkol Videoscribe Tema Gelombang pada Kehidupan Sehari-hari Untuk Melatih Kemampuan Argumentasi Siswa - Amaliah, Kholisotul; Nulhakim, Lukman; Berlian, Liska (PendIPA Journal of Science Education, 2025)
This research was conducted to produce a valid Sparkol Videoscribe based on the ability to argue the theme of wave utilization in students' daily lives and describe student responses to Sparkol Videoscribe based on the ability to argue the theme of wave utilization in students' daily lives. The method used is the Research and Development (R&D) method. The development model used by the 4-D model has stages of define, design, and develop. The instruments used were interview questionnaires, student response questionnaires, and validation questionnaires. Data analysis is descriptive, quantitative and qualitative. The results of the learning video validation assessment were obtained from 85.20% (very valid), 81.52% (very valid), and 91.48% (very valid) science teacher validators. The results of the student response rate showed a percentage score with an average of 85.42% (strongly agree). With this, it can be concluded that Sparkol Videoscribe -based learning videos on the theme of Waves in Everyday Life can be used by students in the science learning process. Keywords: Learning Video, Sparkol Videoscribe , Argumentation Ability.